(3CSGSjGJ GdJSYjQ aj GdJShjb GdeYGUQs (3eONd Sdhcis - (3YHjOGJ(B, (3eMeO GHQGgjes ((3YeGfs (3OGQ GdeSjQIs, 2004)
(3ebOeI aj GdJSYjQ(B/ (3JCKjQ GdHjFI GdGbJUGOjI aj YedjI GdJSYjQ, MSH GdOhQI GdGbJUGOjI hOhQI MjGI GdSdYI, JSYjQ SdY GdeSJgdc GdfgGFj hGdUfGYj hGdNOeGJ (B((3GdGYJHGQGJ hGdeJWdHGJ(B)(3, GdJSYjQ GdOhdj, OhQ GdOQGSGJ hGdHMhK aj YedjI GdJSYjQ, GdJSYjQ Hjf Gdeaghejf GdGSdGej hGdQCSeGdj, GdJSYjQ Ydi GdGfJQfjJ, MGdGJ YedjI aj GdJSYjQ(B.s
Keywords: (3COGQI GdeHjYGJs; (3GdJShjbs